(untitled) (Comprehensive Journal of Science, 2025)
One of the most important things a commentator relies on in interpreting and explaining Quranic verses is poetic evidence. Among the Companions who followed this approach was our master Ibn Abbas - may God be pleased with them both - to understand the unusual aspects of the Holy Quran. Sheikh Abu Bakr al-Haddad followed this approach in his commentary and he was distinguished by his use of poetic evidence. He differs from other commentators, relying on transmission based on opinion and knowledge.